2020
DOI: 10.1002/adma.202005476
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular‐Matrix‐Reinforced Bioinks for 3D Bioprinting Human Tissue

Abstract: Recent advances in 3D bioprinting allow for generating intricate structures with dimensions relevant for human tissue, but suitable bioinks for producing translationally relevant tissue with complex geometries remain unidentified. Here, a tissue‐specific hybrid bioink is described, composed of a natural polymer, alginate, reinforced with extracellular matrix derived from decellularized tissue (rECM). rECM has rheological and gelation properties beneficial for 3D bioprinting while retaining biologically inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 46 publications
1
139
0
Order By: Relevance
“…Recombinantly produced biomaterials such as the elastin-like recombinamer polymer allows for the precise composition of structural and chemical properties, with gene technology introducing sequences for cell attachment and MMP degradation and at the same time exposing functional groups for binding of for example growth factors to promote or maintain the MSC therapeutic effect (Ibáñez-Fonseca et al, 2020). De Santis et al recently demonstrated the functional outcome of a 3D bioprinted hybrid hydrogel combining decellularized lung tissue with alginate to form human airways containing primary human airway epithelial progenitor cells (De Santis et al, 2020). Transplanted in mice, the cells showed evidence of differentiation into mature epithelial cells.…”
Section: Hydrogel Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinantly produced biomaterials such as the elastin-like recombinamer polymer allows for the precise composition of structural and chemical properties, with gene technology introducing sequences for cell attachment and MMP degradation and at the same time exposing functional groups for binding of for example growth factors to promote or maintain the MSC therapeutic effect (Ibáñez-Fonseca et al, 2020). De Santis et al recently demonstrated the functional outcome of a 3D bioprinted hybrid hydrogel combining decellularized lung tissue with alginate to form human airways containing primary human airway epithelial progenitor cells (De Santis et al, 2020). Transplanted in mice, the cells showed evidence of differentiation into mature epithelial cells.…”
Section: Hydrogel Encapsulationmentioning
confidence: 99%
“…Transplanted in mice, the cells showed evidence of differentiation into mature epithelial cells. The hydrogel properties both had matched biomechanical properties and contained ECM instructive factors from the native lung tissue (De Santis et al, 2020). Hydrogels based on collagen type I, one of the major structural components of tissues, has been extensively explored in combination with other materials such as silk, a highly elastic protein, to improve the mechanical properties to mimic the viscoelastic properties of tissues (Sanz-Fraile et al, 2020).…”
Section: Hydrogel Encapsulationmentioning
confidence: 99%
“…Epithelial progenitor cells were seeded into this hybrid bioink and 3D printed as a hollow tube and then subjected to ALI differentiation for 28 days. The study found that the hybrid bioink allowed for the differentiation of progenitor cells into ATUB-expressing ciliated cells and that the constructs remained stable and patent for the full 28 days (60). In contrast, culturing human lung organoids (HLOs) derived from pluripotent stem cells within Matrigel enabled cells to spontaneously form physiologically elaborate 3D structures in vitro.…”
Section: Patient-derived Cells For Studying Respiratory Diseasementioning
confidence: 99%
“…Biomaterial inks have been developed from regenerated silk fibroin (SF) and 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized bacterial cellulose (OBC) nanofibrils and engineered for 3D printing of lung tissue scaffolds ( Huang et al, 2020 ). Another group has developed a tissue-specific hybrid bioinks from the naturally occurring polymer alginate along with ECM derived from decellularized tissue ( De Santis et al, 2021 ). In both models HBECs were able to adhere and proliferate, maintaining expression of basal cell markers TP63 and KRT5.…”
Section: Introductionmentioning
confidence: 99%
“…In both models HBECs were able to adhere and proliferate, maintaining expression of basal cell markers TP63 and KRT5. De Santis and colleagues evaluated differentiation over a month on 3D bio-printed human airways composed of regionally specified airway smooth muscle and human bronchial epithelial cells and observed basolateral localization of BCs and evidence of differentiation to mucus-producing cells (MUC5AC + ) and ciliated cells shown directly through scanning electron microscopy and alpha-tubulin expression ( De Santis et al, 2021 ). The results of this study do demonstrate that a combination of exogenously and endogenously derived ECM materials supports epithelial development and offers the potential of printing customized airway scaffolds which has not yet been achieved with native ECM alone.…”
Section: Introductionmentioning
confidence: 99%